Pengaruh Brand Image Dan Kualitas Pelayanan Terhadap Keputusan Pembelian : (Survei Pada Konsumen Kedai Fullhopper Tasikmalaya) - Annisa Sajdah Maulana (CV. ULIL ALBAB CORP, 2022)
This study aims to analyze the influence of brand image and service quality on purchase decisions (survey of Tasikmalaya fullhopper store consumers). The research method used is quantitative descriptive method with a survey approach with a sample of 100 respondents. Data analysis in this study used multiple linear regression analysis, correlation, and coefficient of determination using SPSS software. The results of his research show that brand image has a positive relationship and has a significant effect on purchasing decisions. While the quality of service has a positive relationship and does not have a significant effect on purchasing decisions.